2021
DOI: 10.1186/s12877-021-02467-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of gait with global cognitive function and cognitive domains detected by MoCA-J among community-dwelling older adults: a cross-sectional study

Abstract: Background Gait was proved to be strongly associated with global cognitive function and multiple cognitive domains; however, previous research usually concentrated on individual gait parameters. This study used wearable sensors to measure gait parameters in different aspects and comprehensively explored the association of gait with global cognitive function and cognitive domains. Methods The data of this cross-sectional study were obtained from 236… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Other studies conducted in Japan, in which the average age of subjects was about 75 yr, showed similar Montreal Cognitive Assessment scores, suggesting that the result reflects old age. 33,34 In this study, since we adopted a diagnostic method for postoperative cognitive dysfunction that has been demonstrated to have excellent sensitivity and specificity in previous studies, 2,14,18 we believe that the relatively low incidence of postoperative cognitive dysfunction after 1 week despite the high percentage (greater than 80%) of patients with preoperative cognitive impairment was not due to a sensitivity issue. Additionally, the incidence of postoperative cognitive dysfunction at 3 months was higher, ranging between 8.5 and 18.4%, depending on the handling of missing data.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies conducted in Japan, in which the average age of subjects was about 75 yr, showed similar Montreal Cognitive Assessment scores, suggesting that the result reflects old age. 33,34 In this study, since we adopted a diagnostic method for postoperative cognitive dysfunction that has been demonstrated to have excellent sensitivity and specificity in previous studies, 2,14,18 we believe that the relatively low incidence of postoperative cognitive dysfunction after 1 week despite the high percentage (greater than 80%) of patients with preoperative cognitive impairment was not due to a sensitivity issue. Additionally, the incidence of postoperative cognitive dysfunction at 3 months was higher, ranging between 8.5 and 18.4%, depending on the handling of missing data.…”
Section: Discussionmentioning
confidence: 82%
“…All participants in this study received home-visit rehabilitation and showed lower physical and cognitive functions than similarly aged community-dwelling citizens. 32 , 37 , 38 , 39 ) In fact, 89% of participants scored below 26 points on MoCA-J, which is an indicator of cognitive decline. Although this study did not identify a clear relationship between cognitive decline and declines in performance in BADLs and IADLs, the impact of cognitive decline on the functional ability of the elderly is significant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the participants of the current study had relatively low levels of physical and cognitive functioning when compared with the total population of community-dwelling elderly citizens, based on previous studies. 32 , 37 , 38 , 39 ) Regarding the ADL measures used in this study, BADLs were assessed using the Barthel Index, and a decline in performance was defined as a BI below 85. 16 ) In contrast, IADLs were assessed using FAI, and a decline in performance was defined as an FAI score lower than 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation